Pengaruh Penggunaan Model Pembelajaran Teams Games Tournament Terhadap Pemahaman Konsep Matematika Kelas X SMK Adi Luhur - Alviana Legista; Hany Shofia; Melati Br Pasaribu; Melinda Dwi Agustina; Nestiana Juin (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2023)
The low student learning outcomes are caused by a lack of ability to understand concepts and many students are not serious about working on questions, so that learning is not optimal and effective. Therefore, the general aim of this research is to describe the influence of TGT type cooperative learning based on badeglar media on the conceptual understanding of class X students at Adi Luhur Vocational School for the 2023/2024 academic year. The method in this research uses a pre-experimental method, namely comparing the results of the pretest and posttest with the research population being all class X students at Adi Luhur Vocational School and the sample used in this research is the population itself. Data was collected using test techniques with test sheet research instruments. The data is processed according to parametric statistical calculations. The results of this research prove that the use of TGT type cooperative learning based on counting funnel media has a positive effect on student learning outcomes. The average percentage of student learning outcomes using t-test calculations where tcount is greater than ttable, namely 3.277 > 1.740. So it can be concluded that H0 is rejected and H1 is accepted, in other words there is a significant difference between the pretest and posttest